ArmMenu: command input on distant displays with proprioception based lateral arm movements. Issue 13 (3rd October 2021) - Tu, Huawei; Huan, Weiyang; Yang, Xingdong; Ren, Xiangshi; Tian, Feng
ABSTRACT: In this paper, we present ArmMenu, a command input approach for distant displays. ArmMenu has a circular interface like pie menus and menu selection is performed by proprioception-based lateral arm movements. We implemented ArmMenu with an off-the-shelf body tracking device (Kinect) and conducted two experiments to validate its efficacy. In the first experiment, we explored the design space of ArmMenu by varying the number of menu items, with exposed or hidden menu modes. Users can operate up to 8-item menus with high selection accuracy (>98%). ArmMenu was fast and accurate even with the hidden menu mode. The second experiment compared the performance of ArmMenu and touchless marking menus. While having similar selection accuracy, ArmMenu was faster and more preferable by users. Our studies consequently demonstrate ArmMenu's effectiveness for command input on distant displays.